A Lingvopoetic Study Of Poetic Imagery Expressed Through Agionyms (Eurasian Research Bulletin, 2023)
In this article, cases where agionymic lexemes are used in the realization of poetic expression and aesthetic evaluation are analyzed. Each prophet's name has expressed a certain concept as a symbol in our classical literature. Poets appropriately used these symbols to express their subjective assessment and created beautiful images